Предмет: Алгебра,
автор: лшкуумф6899
Уравнение: 5-6•(x-1)=2•(2x+3)-1
Ответы
Автор ответа:
2
5-6*(x-1)=2*(2x+3)-1
5-6x+6=4x+6-1
5-6x=4x-1
-6x-4x=-1-5
-10x=-6
x=3/5
x=0.6
5-6x+6=4x+6-1
5-6x=4x-1
-6x-4x=-1-5
-10x=-6
x=3/5
x=0.6
Автор ответа:
0
5-6x+6=4x+6-1
11-6x=4x+5
-6x-4x=5-11
-10x=-6
10x=6
x=6/10
x=0,6
11-6x=4x+5
-6x-4x=5-11
-10x=-6
10x=6
x=6/10
x=0,6
Похожие вопросы
Предмет: История,
автор: vitaddlo
Предмет: Алгебра,
автор: sergejpigulak
Предмет: Математика,
автор: 4n42njsgm6
Предмет: Математика,
автор: 890света098
Предмет: Математика,
автор: mamajanowadili